'Mediators mediating themselves': tensions within the family mediator profession. (March 2023) - Blakey, Rachael
Abstract: The demand for family mediation to adapt and change has risen sharply in the contemporary English and Welsh family justice system. This paper focuses on a crucial, yet overlooked, barrier to reform: the tensions felt within the family mediator profession. It first provides an important overview of the introduction of family mediation in the late twentieth century, highlighting the distinction between the traditional therapeutic mediator and the subsequent lawyer mediator. Recent anecdotal evidence suggests that friction exists amongst the two mediator sub-groups, similar to earlier tensions felt between lawyers and mediators. The remainder of this paper is based on an empirical study, comprising 17 interviews with family mediators, which confirms these tensions, as well as a lack of national identity across the profession. However, the data also reveal mediators' desire for collaboration and community within the profession. The paper is hopeful that regulatory reform can help mediators to 'mediate themselves' going forward, and questions whether this transition is supported by a new hybrid mediator.